A novel approach for the efficient modeling of material dissolution in electrochemical machining. (15th October 2021) - van der Velden, Tim; Rommes, Bob; Klink, Andreas; Reese, Stefanie; Waimann, Johanna
Abstract: This work presents a novel approach to efficiently model anodic dissolution in electrochemical machining. Earlier modeling approaches employ a strict space discretization of the anodic surface that is associated with a remeshing procedure at every time step. Besides that, the presented model is formulated by means of effective material parameters. Thereby, it allows to use a constant mesh for the entire simulation and, thus, decreases the computational costs. Based on Faraday's law of electrolysis, an effective dissolution level is introduced, which describes the ratio of a dissolved volume and its corresponding reference volume. This inner variable allows the modeling of the complex dissolution process without the necessity of computationally expensive remeshing by controlling the effective material parameters. Additionally, full coupling of the thermoelectric problem is considered and its linearization and numerical implementation are presented. The model shows good agreement with analytical and experimental validation examples by yielding realistic results. Furthermore, simulations of a pulsed electrochemical machining process yield a process signature component of the surface roughness related to the specific accumulated electric charge. The numerical examples confirm the simulation's computational efficiency and accurate modeling qualities.